Metamifop as an estrogen-like chemical affects the pituitary-hypothalamic-gonadal (HPG) axis of female rice field eels (Monopterus albus) - Zhang, Yi; Guan, Tianyu; Wang, Long; Ma, Xintong; Zhu, Chuankun; Wang, Hui; Li, Jiale (Frontiers in Physiology, 2023)
Metamifop (MET) is a widely used herbicide. It is likely for it to enter water environment when utilized, thus potential impacts may be produced on aquatic animals. Little information is available about its effects on the endocrine system of fish to date. In the current study, female rice field eels (Monopterus albus) were exposed to different MET concentrations (0, 0.2, 0.4, 0.6, 0.8 mg L 1) for 96 h to examine the effect of MET on the hypothalamic-pituitary-gonadal (HPG) axis and sexual reversal. The results showed that high concentrations of MET exposure increased vitellogenin (VTG) levels in liver and plasma, but plasma sex hormone levels were not affected by MET exposure. MET exposure increased the expression of CYP19A1b and CYP17 that regulate sex hormone production in the brain, but the expression of genes (CYP19A1a, CYP17, FSHR, LHCGR, hsd11b2, 3β-HSD) associated with sex hormone secretion in the ovary and the estrogen receptor genes (esr1, esr2a, esr2b) in the liver were all suppressed. In addition, the expression of sex-related gene (Dmrt1) was suppressed. This study revealed for the first time that MET has estrogen-like effects and has a strong interference with the expression of HPG axis genes. MET did not show the ability to promote the sexual reversal in M. albus, on the contrary, the genes expression showed that the occurrence of male pathway was inhibited.